2017
DOI: 10.1124/dmd.116.072231
|View full text |Cite
|
Sign up to set email alerts
|

Regional Expression Levels of Drug Transporters and Metabolizing Enzymes along the Pig and Human Intestinal Tract and Comparison with Caco-2 Cells

Abstract: Intestinal transporter proteins and metabolizing enzymes play a crucial role in the oral absorption of a wide variety of drugs. The aim of the current study was to characterize better available intestinal in vitro models by comparing expression levels of these proteins and enzymes between porcine intestine, human intestine, and Caco-2 cells. We therefore determined the absolute protein expression of 19 drug transporters and the mRNA expression of 12 metabolic enzymes along the pig intestinal tract (duodenum, j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
60
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 29 publications
3
60
1
Order By: Relevance
“…In line with our previous analysis, OATP1A2 could not be detected in any intestinal segment (data not shown), which argues against its involvement in interaction studies with juices or drugs, as frequently discussed . Our results also corroborate observations of other authors …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with our previous analysis, OATP1A2 could not be detected in any intestinal segment (data not shown), which argues against its involvement in interaction studies with juices or drugs, as frequently discussed . Our results also corroborate observations of other authors …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we could verify the distinct increase in P‐gp, BCRP, and PEPT1 proteins from proximal to distal small intestine, which is expected to significantly affect oral drug absorption, as discussed elsewhere . However, the obtained quantitative data cannot be directly compared to currently available studies, as those studies analyzed enriched membrane fractions but not whole‐tissue lysates . However, correlation analysis of the present data with our previous study demonstrated significant correlation ( R > 0.7) of transporter protein abundance in the duodenum, ileum, and colon (data not shown).…”
Section: Discussionmentioning
confidence: 46%
“…Our data confirmed that CYP3A4 and CYP2C9 are the major CYP enzymes in the human small intestine, whereas the expression of CYP2C19, CYP2B6, CYP3A5 and CYP2D6 is substantially lower . In a very recent study, we could confirm these findings also on small intestinal protein levels in a different cohort of nine donors in which we characterized the intestinal and hepatic abundance of clinically relevant metabolizing enzymes (CYP3A4 > CYP2C9 > CYP2C19 > CYP2D6 ~ CYP2B6 > CYP3A5) …”
Section: Discussionsupporting
confidence: 83%
“…Our data confirmed that CYP3A4 and CYP2C9 are the major CYP enzymes in the human small intestine, whereas the expression of CYP2C19, CYP2B6, CYP3A5 and CYP2D6 is substantially lower. 18,20,33,44,45 In a very recent study, we could confirm these findings also on small intestinal protein levels in a different cohort of nine donors in which we characterized the intestinal and hepatic abundance of clinically relevant metabolizing enzymes (CYP3A4 > CYP2C9 > CYP2C19 > CYP2D6C YP2B6 > CYP3A5). 46 In line with this observation, CYP3A4 and CYP2C9 substrates (eg, for CYP3A4: midazolam, nifedipine, simvastatin, cyclosporine, tacrolimus, sirolimus, lopinavir, ritonavir; for CYP2C9: tolbutamide, diclofenac, warfarin) were shown to undergo substantial first-pass metabolism.…”
supporting
confidence: 62%
See 1 more Smart Citation